Model Hot Fit (Human, Organization, Technology Fit) Untuk Evaluasi Penerapan Aplikasi SATUSEHAT - Dewi Lusiana; Agung Nilogiri (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2023)
SATUSEHAT is an application that integrates patient medical records data in healthcare facilities that are part of Indonesia Health Services (IHS). Evaluating the success of the SATUSEHAT application is essential. The Hot Fit model (Human, Organization, Technology Fit) is used to assess the success of implementing the SATUSEHAT application. The research objective is to determine the level of success of the SATUSEHAT application using the Evaluation Framework (HOT - FIT) Model. The data analysis method uses the Structural Equation Model (SEM) to test hypotheses, instrument validity, and reliability. The sample consists of 100 SATUSEHAT users. The research findings indicate that Service Quality (SQ) significantly impacts User Satisfaction (US). It means that the better the service, the quicker and more responsive it is, the higher the user satisfaction. User Satisfaction (US) significantly influences Net Benefit (NB). In other words, as the application's benefits improve, so does user satisfaction. Organizational Structure also significantly affects Net Benefit (NB). It implies that the application's benefits are enhanced by effective corporate management. The research results demonstrate that the use of the SATUSEHAT application is successful, and the application's features meet user needs.